The Dust Bowl : an interactive history adventure - Lassieur, Allison (Mankato, Minn. : Capstone Press, 2009)
"Describes the people and events of the U.S. Dust Bowl. The reader's choices reveal the historical details from the perspectives of a farmer, a migrant worker, and a government photographer"--Provided by publisher.
Includes bibliographical references and index.
edited hb 2015-06-16
Keywords: Depressions -- 1929 -- Great Plains -- Juvenile literature; Documentary photography -- Great Plains -- History -- 20th century -- Juvenile literature; Droughts -- Great Plains -- History -- 20th century -- Juvenile literature; Dust Bowl Era, 1931-1939 -- Juvenile literature; Dust storms -- Great Plains -- History -- 20th century -- Juvenile literature; Farm life -- Great Plains -- History -- 20th century -- Juvenile literature; Farmers -- Great Plains -- History -- 20th century -- Juvenile literature; Migrant labor -- Great Plains -- History -- 20th century -- Juvenile literature; Photographers -- United States -- History -- 20th century -- Juvenile literature; Great Plains -- Social conditions -- 20th century -- Juvenile literature